Rethinking agricultural funding in North Africa to meet the needs of all farmers - (:unkn) unknown (My University, 2011)
Agricultural funding has been one of the favoured instruments for transforming North African agriculture. However, agricultural funding systems continue to reflect the countries’ social problems, and economic contradictions, as well as the limits to the management of rare natural resources, which have now been reached. These agricultural sectors are faced with the problem of climate change and the need to guarantee food security, which has been severely compromised by the volatility of international prices of basic foodstuffs supplied to markets and local processing industries. The funding on which investment capacity depends is still the favoured instruments for dealing with these problems. What is the diagnosis of the current situation, what are its main limitations, and how is the system to be reformed so that it benefits small farmers in North Africa and offers a new model for much-needed agricultural growth?
Keywords: African Research